Mechanistic model coupling gas exchange dynamics and Listeria monocytogenes growth in modified atmosphere packaging of non respiring food. (October 2015) - Chaix, E.; Broyart, B.; Couvert, O.; Guillaume, C.; Gontard, N.; Guillard, V.
Abstract: A mechanistic model coupling O2 and CO2 mass transfer (namely diffusion and solubilisation in the food itself and permeation through the packaging material) to microbial growth models was developed aiming at predicting the shelf life of modified atmosphere packaging (MAP) systems. It was experimentally validated on a non-respiring food by investigating concomitantly the O2 /CO2 partial pressure in packaging headspace and the growth of Listeria monocytogenes (average microbial count) within the food sample. A sensitivity analysis has revealed that the reliability of the prediction by this "super-parametrized" model (no less than 47 parameters were required for running one simulation) was strongly dependent on the accuracy of the microbial input parameters. Once validated, this model was used to decipher the role of O2 /CO2 mass transfer on microbial growth and as a MAP design tool: an example of MAP dimensioning was provided in this paper as a proof of concept. Highlights: We model the dynamic of gas exchange in the food/packaging system. We decipher the role of gas transfer on Listeria monocytogenes growth. Increasing precision on microbial parameters will increase model accuracy. Our model can be used as Decision Support System for packaging dimensioning. O2 /CO2 transfer could not be neglected when permeable packaging are used.